Gregory the Great and the Bestiary - Kerns, Brian (Cistercian studies quarterly, 2011)
The article explores the influence of Saint Gregory the Great on medieval bestiaries. The literary piece by R. G. Hesbert titled "Le Bestiaire de Grégoire" is highlighted which examines the spirituality of Saint Gregory. The book "Moralia in Job," by Saint Gregory is also outlined which reveals a concept of bestiary in his theological teachings.